2022
DOI: 10.1002/mp.15973
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical comparison of energy‐resolved and digital‐subtraction angiography

Abstract: Background X‐ray coronary angiography is a sub‐optimal vascular imaging technique because it cannot suppress un‐enhanced anatomy that may obscure the visualization of coronary artery disease. Purpose The purpose of this paper is to evaluate the theoretical image quality of energy‐resolved x‐ray angiography (ERA) implemented with spectroscopic x‐ray detectors (SXDs), which may overcome limitations of x‐ray coronary angiography. Methods We modeled the large‐area signal‐difference‐to‐noise (SDNR) of contrast‐enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 51 publications
2
11
2
Order By: Relevance
“…We showed that DSA was optimized when the tube voltage was in the range of 90 to 100 kV, which is higher than the theoretical optimal tube voltages reported by Tanguay et al 1 . and Aubert et al 3 . These theoretical studies however did not account for x‐ray scatter, which likely affects the optimal tube voltage.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…We showed that DSA was optimized when the tube voltage was in the range of 90 to 100 kV, which is higher than the theoretical optimal tube voltages reported by Tanguay et al 1 . and Aubert et al 3 . These theoretical studies however did not account for x‐ray scatter, which likely affects the optimal tube voltage.…”
Section: Discussioncontrasting
confidence: 54%
“…Single-exposure DE angiography would not be susceptible to motion artifacts because only a single x-ray exposure is required. Additionally, unlike kV-switching DE angiography, single-exposure DE angiography does not require heavy beam filtration 1,3,4,17 and therefore may be less constrained by the tube loading limitations that compromise image quality in kV-switching DE angiography. Regarding image quality, in a theoretical study, Tanguayet al 1 investigated single-exposure DE angiography assuming ideal PCDs, and showed that such an approach would enable suppressing soft tissues from angiography images with an iodine SDNR nearly equal to that of kV-switching DE angiography and DSA for matched patient exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Larger reductions in image quality are expected for systems that do not implement ACS for charge-sharing correction. For example, in a study of contrast-enhanced vascular imaging, Aubert et al 41 showed that removing ACS degraded iodine SNR by a factor of two. Given that the count rates in mammography are low enough to be able to use ACS with negligible pulse pile-up, that ACS technology is available, and that not using ACS will likely result in substantial image quality reductions,we expect ACS to be implemented if CdTe PCDs become clinically-available.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that, in theory, ideal photon counting x‐ray detectors can suppress soft‐tissues and produce iodine CNR almost equal to that of DSA and DE kV‐switching approaches for matched patient exposures 15 . More recently, we investigated the effect of charge sharing and other non‐idealities, including electronic noise and non‐unity quantum efficiency, on the image quality of x‐ray angiography implemented with cadmium telluride (CdTe) photon‐counting x‐ray detectors 20,21 . We investigated three‐material decompositions that suppress bone and soft‐tissue but found substantial reductions in image quality relative to DSA, even for ideal photon‐counting detectors.…”
Section: Introductionmentioning
confidence: 99%
“…15 More recently, we investigated the effect of charge sharing and other non-idealities, including electronic noise and non-unity quantum efficiency, on the image quality of x-ray angiography implemented with cadmium telluride (CdTe) photon-counting x-ray detectors. 20,21 We investigated three-material decompositions that suppress bone and soft-tissue but found substantial reductions in image quality relative to DSA,even for ideal photon-counting detectors.…”
Section: Introductionmentioning
confidence: 99%